IS INTERPROFESSIONAL PRACTICE (IPP) FOCUSED ON MEDICATION SAFETY FEASIBLE IN INDONESIA? A QUALITATIVE STUDY - Desak Ketut Ernawati; Ya Ping Lee; Bruce Sunderland; Jeff Hughes (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
This paper explores facilitators for and barriers to the implementation of IPP focusing on medication safety in a public hospital in Bali, Indonesia. Qualitative methods involved interviews with stakeholders from a university and a hospital and focus group discussions with healthcare professionals in the hospital. Semi-structured questions were developed as a guide for the interviews and discussions. All interviews and discussions were recorded. The six steps of Braun and Clarke’s thematic analysis methodology were implemented in determining the themes. The Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist was employed in reporting of findings. Participants indicated that support from the government and perceived benefits of IPP were facilitators for IPP. However, the participants mostly mentioned the barriers of IPP including lack of competencies for IPP and lack of understanding of the role of other healthcare professionals as barriers to the implementation of IPP. This showed that these were the barriers identified to the implementation of IPP in the study hospital. Despite the fact that participants were supportive of IPP, the participants identified some barriers to the implementation of IPP in the study hospital. The implementation requires support of the government, professional organisations, and stakeholders at the university and hospital levels.